P57 AIR GAP in neurointerventions – a reduction of radiation dose and exposure. (29th August 2022) - Pilgram-Pastor, S; Slotboom, J; Branca, M; Piechowiak, EI; Dobrocky, T; Petroulia, V; Kaesmacher, J; Gralla, J; Mordasini, P
Abstract : Introduction: There are two methods to suppress scatter radiation: Anti scatter grids and air gap technique. Air gap technique stands for a large distance between the patient and the detector. Aim of study: In this study, both methods (Anti scatter grid or Air gap) are compared for neurointerventions. Methods: The analysis was performed for a controlled comparison of clinical radiation dose utilization. A DSA run was done under usual settings with an anti scatter grid and detector close to the object. The DSA run was than repeated for clinical reasons without the antiscatter grid and an increased focus to detector distance (SID). To measure radiation dose exposure three dosimeter were installed and weared by the interventionalist as well as they were fixed in the angio suite at the side of the detector or radiation tube. Results: In total 12 pairs of DSA runs were analysed in 6 different patients and interventions. To use air gap instead of an antiscattered grid reduced radiation dose up to 39% (ratio mean 0, 61, SD 0, 12), this account also for DAP values. Measurement of the equivalent dose recorded at fixed points in the angio suite also showed significant less dosis at the real time dosimeter recordings (33% less equivalent dosis next to the tube, 23% less equivalent dosis next to the detector). The overall quality of the image was detected by all raters more than 95% as good/very good. Conclusion: Air gap in neurointerventions can reduce radiation dose and exposure without compromise of image quality. References: Partridge J, Mcgahan G, Causton S, Bowers M, Mason M, Dalby M, Mitchell A. Radiation dose reduction without compromise of image quality in cardiac angiography and intervention with the use of a flat panel detector without an antiscatter grid. Heart 2006 Apr;92 (4):507–10. DOI: 10.1136/HRT.2005.063909. EPUB 2005 SEP 13. Do you have any conflict of interest to declare? : No